2006
DOI: 10.1158/1535-7163.mct-05-0358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined DNA repair inhibition and G2 checkpoint inhibition on cell cycle progression after DNA damage

Abstract: In response to DNA damage, cell survival can be enhanced by activation of DNA repair mechanisms and of checkpoints that delay cell cycle progression to allow more time for DNA repair. Inhibiting both responses with drugs might cause cancer cells to undergo cell division in the presence of lethal amounts of unrepaired DNA. However, we show that interfering with DNA repair via inhibition of DNAdependent protein kinase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Cell cycle G 2 checkpoint abrogation is also an attractive strategy for sensitizing cancer cells to DNA-damaging anticancer agents without increasing adverse effects on normal cells. 60 Interestingly, a recent report has suggested that G 2 checkpoint inhibitors may be most effective at an earlier stage in the cell cycle, 61 a stage that may correspond to what has been reported to be regulated by E2F4. 3 Genome-wide analysis of E2F-dependent transcriptional regulation has identified many potential gene targets.…”
Section: Resultsmentioning
confidence: 95%
“…Cell cycle G 2 checkpoint abrogation is also an attractive strategy for sensitizing cancer cells to DNA-damaging anticancer agents without increasing adverse effects on normal cells. 60 Interestingly, a recent report has suggested that G 2 checkpoint inhibitors may be most effective at an earlier stage in the cell cycle, 61 a stage that may correspond to what has been reported to be regulated by E2F4. 3 Genome-wide analysis of E2F-dependent transcriptional regulation has identified many potential gene targets.…”
Section: Resultsmentioning
confidence: 95%
“…5,30,[37][38][39] This arrest is reversible-most cells resume cell cycle progression spontaneously by 24 hrs post-IR. G 2 -arrested cells can be forced to enter mitosis prematurely when treated with G 2 checkpoint kinase inhibitors between 16 and 24 hrs after IR.…”
Section: Resultsmentioning
confidence: 99%
“…G 2 -arrested cells can be forced to enter mitosis prematurely when treated with G 2 checkpoint kinase inhibitors between 16 and 24 hrs after IR. 5,30,[37][38][39] To determine whether treatment with checkpoint inhibitors of G 2 -arrested cells lacking p53 function provides radiosensitization, HCT116p53 -/-and MCF-7mp53 cells were irradiated with 0, 2, 4 or 6 Gy and 16 hrs later exposed for 8 hrs (i.e., 16-24 hrs) to concentrations of caffeine (2 mM) or isogranulatimide (10 mM), known to cause maximal G 2 checkpoint abrogation between 16 and 24 hrs after IR (see Fig. 1 for an overview of the experimental design).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while it seemed reasonable that inhibition of DNA-PK and the G2 cell cycle checkpoint would have synergistic antitumor effects, Sturgeon et al (2006) reported that inhibition of DNA-PK reduces the ability of checkpoint inhibitors to abrogate G2 arrest. The authors hypothesized that 'DNA repair inhibition elicits abnormally strong checkpoint signaling that causes essentially irreversible G2 arrest and strongly reduces the ability of checkpoint kinase inhibitors to overcome G2 arrest and radiosensitize cells' (Sturgeon et al, 2006). Perhaps, this G2 arrest is aided by activation of the alternative NHEJ pathway, thus rendering escape from G2 arrest by inhibitors inefficient.…”
Section: Combinations Of Dna-repair Inhibitorsmentioning
confidence: 99%